The Connection and Development of Unpredictability and Sensitivity in Maternal Care Across Early Childhood - Holmberg, Eeva; Kataja, Eeva-Leena; Davis, Elysia Poggi; Pajulo, Marjukka; Nolvi, Saara; Hakanen, Hetti; Karlsson, Linnea; Karlsson, Hasse; Korja, Riikka (Frontiers in Psychology, 2022)
Both patterns of maternal sensory signals and sensitive care have shown to be crucial elements shaping child development. However, research concerning these aspects of maternal care has focused mainly on maternal sensitivity with fewer studies evaluating the impact of patterns of maternal behaviors and changes in these indices across infancy and childhood. The aims of this study were to explore how maternal unpredictability and sensitivity develop and associate with each other from infancy to toddlerhood and whether elevated maternal depressive and anxiety symptoms relate to maternal unpredictability and sensitivity in toddlerhood. The study population consisted of 356 mother-child dyads assessed at 30 months; a subset of 103 mother-child dyads additionally participated in 8 months assessment. Maternal unpredictability and sensitivity were assessed from video-recorded free-play episodes at 8 and 30 months. Maternal depressive and anxiety symptoms were assessed with questionnaires 14, 24, 34 weeks’ GA and 3, 6, 12 and 24 months. Mean level of mothers’ unpredictability decreased on average whereas sensitivity did not change between infancy and toddlerhood. Both maternal unpredictability and sensitivity showed moderate level of individual stability from infancy to toddlerhood and these two measures were modestly correlated within each age. Elevated maternal depressive and anxiety symptoms were not related to unpredictability but related to lower maternal sensitivity in toddlerhood. These results identify unpredictability as a characteristic of parental care that is independent of standard quality measures and suggest that it may be less influenced by maternal depressive and anxiety symptoms.